Fracture Risk Assessment Tool (Frax Tool) Scores in Type 2 Diabetes Mellitus Patients in Haji Hospital Medan - T. Shafira; Rangkuti, Deske Muhadi; Laksmi, Lidya Imelda; Rachmatsyah, M. Yusuf (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2024)
Background: Diabetes mellitus (DM) is a metabolic disease characterized by chronic hyperglycemia resulting from defects in insulin secretion and/or insulin action. Bone fragility in T2DM, which mirrored bone mineral density and bone mass reduction. Classical diagnosis of osteoporosis in T2DM is performed by dual-energy X-ray absorptiometry (DXA) and the risk of fracture can be assessed using the FRAX tool (Fracture Risk Assessment Tool). The purpose of the study was to assess the risk of osteoporosis using FRAX tool calculation (without BMD) in T2DM patients at the endocrine metabolic clinic of Haji Hospital Medan. Method: Descriptive observational with a cross-sectional study approach using primary and secondary data from the medical records of the Endocrine and Metabolic Clinic of Haji Hospital Medan in September-October 2023.Results: Of the 80 respondents with a risk of major osteoporosis, there were 77 respondents (96.3%) with low risk, 3 respondents (3%) with moderate risk, and no respondents with high risk (0%). The FRAX score for the risk of hip fracture received a low risk of 72 respondents (90%). At the same time, the high-risk was 8 respondents (10%).Conclusion: The majority of T2DM patients at Haji Hospital Medan are at low- risk for major osteoporosis and hip fracture